Efficacy and Safety of Thrombolytic Therapy in Mongolian Young Adults with Acute Ischemic Stroke - Gongor, Baigalmaa; Tsagaankhuu, Delgermaa; Banzrai, Chimedlkham; Guntev, Tsagaankhuu (Central Asian Journal of Medical Sciences, 2023)
Objectives: The study aimed to assess the safety and efficacy of intravenous thrombolysis (IVT) in Mongolian young patients with acute ischemic stroke (AIS). Methods: Data of 30 AIS patients aged <50 years who were treated with IVT between 2013 and 2023 at the Stroke Department of Third Central Hospital were retrospectively analyzed. For outcome comparison, 60 controls with AIS not treated with IVT and 60 older controls (>50 years) treated with IVT matched age, gender and baseline NIHSS score were selected. Functional outcome at three (3) months defined as “Favorable” and “Unfavorable” (modified Rankin Scale score 0-1 vs 2-6). Symptomatic intracerebral hemorrhage (sICH) was defined according to the SITS-MOSTStudy. Results: “Favorable” outcome at 3 months was significantly higher in young IVT-treated patients (53.3% vs 30.0%, p < 0.05) compared with their matched young and older controls treated with IVT (53.3% vs 26.7%, p = 0.019). The sICHoccurred in 3% of young IVT-treated patients and in 5% of older controls but this difference was nonsignificant. Mortality rate was 21.7% (p = 0.245) among older controls, whereas in young IVT-treated and matched young controls 10% during the 3months follow-up. Conclusions: IVT is safe and beneficial for Mongolian young adults with AIS.